Seismic simulation of three- storey glulam framed structures with mortise and tenon design - Chua, Geraldine Jia Xuan (2024)
This thesis investigates the seismic behaviour of glulam framed structures utilising mortise and tenon joinery, aiming to analyse stress concentration areas and compare the seismic performance with reinforced concrete (RC) buildings. The study focusses on evaluating the strength and weaknesses of glulam structure during earthquake events. A comprehensive analysis of stress distribution and structural integrity is conducted using finite element modelling techniques. The glulam framed structures are designed with fixed supports and incorporate mortise and tenon design without additional components such as slabs and footings. Through detailed simulations and seismic analysis, this research aims to provide insights into the performance of glulam framed structures and their comparative advantages and limitations in seismic conditions.